Freising and the Slavs: Possible Literary Witnesses of the Freising Mission in Carantania Found in Present Day Carinthia - Anke Lenssens (Slavistična Revija, 2023)
More than sixty years ago, four Carolingian fragments from religious manuscripts were discovered in Carinthia. The research done on these fragments was only superficial. Three of the discovered fragments can be linked to the mission conducted by the diocese of Freising. We know the Bavarian diocese of Freising was an active player in the Carantanian missionary field, but it is hard to tell how extensive their missionary area was and when they began to contribute to the conversion. The reinvestigation of these fragments is an important step in the reconstruction of the Freising missionary efforts towards the Carantani as they form evidence of missionary activity.